- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 3,066

$\tiny{2.1.5.1}$

Change the second-order initial-value problem into a system of equations

$x''+6x'-2x= 0\quad x(0)=1\quad x'(0)=1$

ok my first step was to do this

$e^{rt}(r^2+6r-2)=0$

using quadratic formula we get

$r=-3+\sqrt{11},\quad r=-3-\sqrt{11}$

just seeing if I going down the right road

Change the second-order initial-value problem into a system of equations

$x''+6x'-2x= 0\quad x(0)=1\quad x'(0)=1$

ok my first step was to do this

$e^{rt}(r^2+6r-2)=0$

using quadratic formula we get

$r=-3+\sqrt{11},\quad r=-3-\sqrt{11}$

just seeing if I going down the right road

Last edited: